A cross-over study of effects on the hypothalamus–pituitary–adrenal (HPA) axis and the sympathoadrenergic system in magnetic field strength exposure from 0 to 7 T. (March 2013) - Gilles, Maria; Paslakis, Georgios; Heinrich, Angela; Szostek, Anne; Meyer, Patric; Nees, Frauke; Rauschenberg, Jaane; Gröbner, Jens; Krumm, Bertram; Semmler, Wolfhard; Flor, Herta; Meyer-Lindenberg, Andreas; et al.
<x xml:space="preserve">Abstract</x> The concept of stress is relevant to magnetic resonance imaging (MRI) examination in various ways. First, levels of stress to staff and patients have not been quantified in ultra-high magnetic fields. Second, research is increasingly interested in experimentally defining regional brain activity during stress. It is therefore important to know whether exposure to the ultra-high static magnetic fields per se might also lead to neurohormonal responses in the hypothalamus–pituitary–adrenal axis and the sympathoadrenal systems. In the present blinded case cross-over study with 41 healthy participants, we measured cortisol not only before and after but also during static magnetic field exposure in MRI scanners. Measures of catecholamines before and after exposure were also part of the study protocol. Using three different field strengths (1.5, 3 and 7 T) and a mock scanner (0 T), we examined whether not only the MRI procedure but also the static magnetic field per se has an influence on the neuroendocrine responses. We found no significant differences in the course of cortisol or catecholamine concentrations between the different static magnetic fields. Our study suggests that the results of MRI studies using stress-paradigms are not influenced by the static magnetic field itself.